Karakteristik Krim Body Scrub Pada Variasi Penambahan Ekstrak Kulit Jeruk Mandarin (Citrus Reticulata) Dan Suhu Pemanasan - Purba, Sevenly Trianisa; Wrastiati, Luh Putu; Triani, I Gusti Ayu Lani (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Body scrub is a cream used to remove dead skin cells and stimulate skin regeneration. This cream is often contains added with natural ingredients that contain active compounds function for skin health and antimicrobial. The process of mixing ingredients for making body scrub cream is influenced by the addition of extracts and the heating temperature of the body scrub cream preparation. This study aims to determine the effect of variations in the addition of mandarin orange peel extract and heating temperature on the characteristics of body scrub cream and to determine the addition of mandarin orange peel extract and certain heating temperatures to produce the best body scrub cream. This study used a two-factorial Randomized Block Design. The first factor is the addition of mandarin orange peel extract (Citrus reticulata) consisting of 3 levels, namely 4.7 and 10% while the second factor is the heating temperature consisting of 3 levels, namely 65.70 and 75°C. Data analysis was carried out by analysis of variance and continued with the Tukey test. The variables observed in this study were pH, viscosity, homogeneity, spreadability, adhesion and organoleptic. The results showed that the addition of mandarin orange peel extract and heating temperature affected pH, viscosity, homogeneity, spreadability, adhesion and organoleptic color, aroma and texture. Based on the effectiveness index test, the addition of 4% extract and heating temperature of 65°C was the best treatment with body scrub cream characteristics of pH 5, viscosity 36,200 cP, homogeneous, spreadability 6.18 cm, adhesion 5.73 seconds, organoleptic color 5.05 (slightly like - like), organoleptic aroma 5.30 (slightly like - like), and organoleptic texture 4,70 (normal-slightly like).